Sinusoidal obstruction syndrome (SOS) related to chemotherapy for colorectal liver metastases: factors predictive of severe SOS lesions and protective effect of bevacizumab. Issue 11 (18th January 2013) - Hubert, Catherine; Sempoux, Christine; Humblet, Yves; van den Eynde, Marc; Zech, Francis; Leclercq, Isabelle; Gigot, Jean‐François
Abstract Objectives The most frequent presentation of chemotherapy‐related toxicity in colorectal liver metastases (CRLM) is sinusoidal obstruction syndrome (SOS). The purpose of the present study was to identify preoperative factors predictive of SOS and to establish associations between type of chemotherapy and severity of SOS. Methods A retrospective study was carried out in a tertiary academic referral hospital. Patients suffering from CRLM who had undergone resection of at least one liver segment were included. Grading of SOS on the non‐tumoral liver parenchyma was accomplished according to the Rubbia‐Brandt criteria. A total of 151 patients were enrolled and divided into four groups according to the severity of SOS (grades 0–3). Results Multivariate analysis identified oxaliplatin and 5‐fluorouracil as chemotherapeutic agents responsible for severe SOS lesions (P < 0.001 and P = 0.005, respectively). Bevacizumab was identified as having a protective effect against the occurrence of SOS lesions (P = 0.005). Univariate analysis identified the score on the aspartate aminotransferase : platelets ratio index (APRI) as the most significant biological factor predictive of severe SOS lesions. Splenomegaly is also significantly associated with the occurrence of severe SOS lesions. Conclusions The APRI score and splenomegaly are effective as factors predictive of SOS. Bevacizumab has a protective effect against SOS.